Long-term clinical outcomes of cardiac resynchronization therapy with or without defibrillation: impact of the aetiology of cardiomyopathy. Issue 11 (25th April 2018) - Leyva, Francisco; Zegard, Abbasin; Umar, Fraz; Taylor, Robin James; Acquaye, Edmund; Gubran, Christopher; Chalil, Shajil; Patel, Kiran; Panting, Jonathan; Marshall, Howard; Qiu, Tian
Abstract: Aims: There is a continuing debate as to whether cardiac resynchronization therapy-defibrillation (CRT-D) is superior to CRT-pacing (CRT-P), particularly in patients with non-ischaemic cardiomyopathy (NICM). We sought to quantify the clinical outcomes after primary prevention of CRT-D and CRT-P and identify whether these differed according to the aetiology of cardiomyopathy. Methods and results: Analyses were undertaken in the total study population of patients treated with CRT-D ( n = 551) or CRT-P ( n = 999) and in propensity-matched samples. Device choice was governed by the clinical guidelines in the United Kingdom. In univariable analyses of the total study population, for a maximum follow-up of 16 years (median 4.7 years, interquartile range 2.4–7.1), CRT-D was associated with a lower total mortality [hazard ratio (HR) 0.72] and the composite endpoints of total mortality or heart failure (HF) hospitalization (HR 0.72) and total mortality or hospitalization for major adverse cardiac events (MACE; HR 0.71) (all P < 0.001). After propensity matching ( n = 796), CRT-D was associated with a lower total mortality (HR 0.72) and the composite endpoints (all P < 0.01). When further stratified according to aetiology, CRT-D was associated with a lower total mortality (HR 0.62), total mortality or HF hospitalization (HR 0.63), and total mortality or hospitalization for MACE (HR 0.59) (all P < 0.001) in patients with ischaemic cardiomyopathy (ICM). There were no differences in outcomes between CRT-D and CRT-P in patients with NICM. Conclusion: In this study of real-world clinical practice, CRT-D was superior to CRT-P with respect to total mortality and composite endpoints, independent of known confounders. The benefit of CRT-D was evident in ICM but not in NICM.